The Labor-Progressive Party in Crisis, 1956–1957 - Levine, Karen (Labour / Le Travail, 2021)
Documents the upheaval inside the Labor-Progressive Party, Canada's major Communist organization, that erupted at its 6th national convention in April 1957, which resulted in an exodus of members from the party. Originally an undergraduate essay, the author's research is based on interviews conducted in 1976-77 with Labor-Progressive Party members who were at the convention.
Keywords: 1956; 20th Congress of the Communist Party of the Soviet Union; Anti-Semitism; Canadian Communism; Gui Caron; J.B. Salsberg; Joseph Stalin; Labor-Progressive Party; Nikita Khrushchev; Norman Penner; Stanley B. Ryerson; Tim Buck

Gender, Space, and Precarious Employment in Canada - Ali, Waad K.; Newbold, K. Bruce (Tijdschrift voor Economische en Sociale Geografie, 2021)
This study aims to examine how gendered precariousness is spatially patterned across Canada's landscape using Statistics Canada's Labour Force Survey. We compare gender differences in distinct precarious forms of employment (PFEs) across a range of geographies, including national, provincial, census metropolitan areas, and urban/rural areas. We find that distinct spatial patterns and degree of gendered precariousness were evident within and across geographic spaces. Logit models further confirmed the robustness of gender differences in PFEs across space, revealing that PFEs were associated with gender, immigration status, age, type of economic family, education, income, and occupation. This study has implications for further understanding the causal factors at play in producing these uneven economic geographies. In terms of policy recommendations, this study calls for greater gender equity in social safety net policies, especially in the wake of the labor market shocks brought by the COVID-19 pandemic.
https://www.researchgate.net/publication/352540101_Gender_Space_and_Precarious_Employment_in_Canada
Keywords: Canada; gender; multiscalar analysis; nonstandard employment; precarious forms of employment; space

The Forgotten Labour of Craft: - Anderson, Benjamin (Labour / Le Travail, 2021)
Over the last decade, firms positioning themselves as craft or artisanal have proliferated in the urban environments of the Global North. Selling themselves as community hubs, friendly neighbours, anticorporate crusaders, and environmental stewards, craft industries – craft breweries, artisanal bakeries, heritage clothing manufacturers, and the like – have effectively insulated themselves from critique. Hidden beneath this veneer, however, are the accounts of countless workers detailing experiences of harassment, overwork, low pay, and discrimination. Motivated by the methodological orientation of workers’ inquiry, this article recounts attitudes and experiences offered by craftworkers and craftspeople about their working conditions, motivations, and attempts to organize in craft industries, particularly craft brewing. Worker testimony reveals a profound disconnect between the optimistic industrial mythologies offered up by craft discourse and the rigid hierarchies, unequal division of labour, and toxic cultures many observed in their workplaces. Contrary to the pervasive artisanal allure that motivates many workers to seek out work in craft brewing and similar industries, the research presented here also suggests new levels of working-class consciousness and solidarity emerging in these industries and profiles attempts by craft brewery workers to organize their workplaces and fight to improve conditions.
Keywords: craft; craft beer; craft industrialism; labour process theory; worker organizing; workers’ inquiry

Workplace Restructuring and Institutional Change: GM Oshawa from 1994 to 2019 - Aquanno, Scott M.; Bryant, Toba (Studies in Political Economy / Recherches en économie politique, 2021)
This paper examines the evolution of three key institutional systems—CAW/UNIFOR unions, General Motors Canada, and the Canadian federal State—and their impact on workplace relations in Oshawa over a 25-year period. It places particular focus on union policies and shows that important opportunities for workplace transition were lost as local and national leaders avoided critical economic issues and failed to seriously contend with changing objective conditions.
Keywords: Free trade; General Motors; Oshawa Ontario; restructuring; union

Applaudissements, remerciements, moyens de bien faire leur travail, qu’attendent les agents hospitaliers comme signes de reconnaissance ? - Baret, Christophe; Kornig, Cathel; Recotillet, Isabelle (Relations industrielles / Industrial Relations, 2021)
La reconnaissance au travail est un des facteurs essentiels de la qualité de vie au travail. Alors que la littérature a mis en évidence la dégradation des conditions de travail à l’hôpital cet article a pour objectif d’étudier les relations entre les conditions de travail et la perception des pratiques de reconnaissance au travail. Nous adoptons l’approche de la reconnaissance en 4 dimensions (existentielle, de la pratique de travail, de l’investissement au travail et des résultats du travail) définie par Brun et Dugas (2005) pour identifier les dimensions qui sont les plus impactées par la transformation des conditions de travail. Nous avons interrogé en entretiens semi-directifs 16 personnels tirés au sort et 5 experts dans un centre hospitalier universitaire français au cours de l’année 2018. Les résultats montrent que la plupart des catégories de personnel regrettent le manque de moyens matériels et humains mis à disposition par la direction pour réaliser un travail de qualité. Ce manque de moyens est perçu comme un manque de reconnaissance de la qualité du travail de la part de la direction de l’établissement. En raison du manque d’effectif, de nombreux personnels accroissent leur investissement pour malgré tout produire des soins de qualité au patient, ils regrettent alors une non reconnaissance de leur investissement au travail. Seules les catégories de personnel les moins qualifiées expriment des attentes de reconnaissance existentielle.
Keywords: conditions de travail; hospital; hôpital; recognition at work; reconnaissance au travail; working conditions

Histoire du Taxi à Montréal : Des taxis jaunes à UberX - Baril, Émile (Labour / Le Travail, 2021)
The article reviews the book, " Histoire du Taxi à Montréal : Des taxis jaunes à UberX," by Jean-Philippe Warren.

Effectivité d’un accord-cadre international : influence des positionnements, des comportements et des interactions des acteurs - Barreau, Jocelyne; Havard, Christelle; Ngaha Bah, Angélique (Relations industrielles / Industrial Relations, 2021)
L’objectif de cet article est d’analyser les facteurs influençant l’effectivité d’un accord-cadre international (ACI). L’effectivité est analysée à l’aune de la mise en conformité des pratiques locales de gestion du travail avec les engagements pris dans l’ACI. Considérant la négociation comme un processus, composé de trois phases (avant-négociation, négociation stricto sensu, après-négociation) et ancré dans un contexte, nous élaborons un modèle d’analyse inspiré des études de processus stratégiques (process studies). Ce modèle met en lumière l’influence des positionnements, des comportements et des interactions des protagonistes de la négociation et de l’application d’un ACI sur son effectivité. Nous détaillons les processus de négociation de quatre ACI, conclus au cours des années 2010, par deux firmes multinationales (FMN) françaises et deux fédérations syndicales internationales (FSI). Ces ACI portent sur des thématiques de gestion du travail (santé et sécurité au travail, égalité femmes-hommes, emploi durable). Cette recherche repose sur une analyse de documents, d’observations et de 38 entretiens, menés auprès de syndicalistes internationaux, européens, nationaux, locaux et de membres des directions générales (DG) de ces FMN. Elle porte une attention particulière à la phase de l’avant-négociation et met en exergue les interactions entre les acteurs managériaux et syndicaux, tout au long du processus de négociation. Nous montrons que le positionnement de la DG de la FMN (« social » ou « managérial ») est un facteur décisif du déroulement de la négociation d’un ACI, de son résultat (accord « substantif ») et de son effectivité. Le positionnement « qualitatif » de la FSI peut être un élément essentiel du déroulement de la négociation (par le choix de la thématique de l’ACI) et de son résultat (dispositions portant sur des sujets sensibles). Enfin, la mobilisation des syndicats locaux, soutenue par la FSI, est essentielle à l’effectivité d’un ACI. Nous révélons des processus d’apprentissage et des particularités des ACI et de la NCI.
Keywords: Accord-cadre international; Effectiveness; Global Union Federation; International Framework Agreement; International collective bargaining; Negotiation process; effectivité; fédération syndicale internationale; négociation collective internationale; processus de négociation

L’école québécoise à l’épreuve de la gestion axée sur les résultats : sociologie de la mise en oeuvre d’une politique néolibérale - Binet, Jonathan (Relations industrielles / Industrial Relations, 2021)
The article reviews the book, "L’école québécoise à l’épreuve de la gestion axée sur les résultats : sociologie de la mise en oeuvre d’une politique néolibérale," by Christian Maroy.

Labour and the Waffle: Unions Confront Canadian Left Nationalism in the New Democratic Party - Blocker, David (Labour / Le Travail, 2021)
In the late 1960s and early 1970s, the Waffle movement in the New Democratic Party (ndp) emerged as a leading proponent of Canadian left economic nationalism. The Waffle, which formed around the “Manifesto for an Independent and Socialist Canada” and challenged the leadership of the ndp from 1969 to 1973, represents a dynamic convergence of many of the social movements that comprised the New Left in Canada. This article examines the evolution of the Waffle’s position on international unionism alongside the reaction of pro-ndp labour leaders to this New Left incursion into the party. NDP-allied labour leaders expressed suspicion and concern for the group’s agenda almost from its inception. The Waffle’s success in appealing to younger and nationalist-minded members of international unions turned suspicion into active opposition. As polarization within the ndp increased, workers’ support for the Waffle within the Canadian labour movement led moderate union leaders to conclude the group must be expunged from the Ontario ndp. Ironically, after the Waffle’s departure from the party the group largely repudiated nationalist breakaways from international unions while, in the ensuing decades, the mainstream labour movement embraced Canadian nationalism.
Keywords: Canadian labour movement; Marxism; New Democratic Party (NDP); New Left; international unions; nationalism; radicalism; sixties

Le dialogue social : un puissant outil régulateur du processus de RSE des entreprises : étude de trois cas en Tunisie - Bouderbala, Amel (Relations industrielles / Industrial Relations, 2021)
L’objectif de cette étude qui a eu lieu dans le contexte tunisien est de comprendre le rôle que peuvent jouer le syndicat et le comité d’entreprise dans le processus de responsabilité sociale de l’entreprise (RSE). La position épistémologique adoptée est interprétativiste et la méthodologie est qualitative, moyennant l’étude de trois cas d’entreprises. Pour mener à bien cette recherche compréhensive, trois outils de collecte de données ont été utilisés : les notes d’observation, les entretiens semi-directifs et les rapports de RSE de l’entreprise.
Keywords: CSR types; Comité d’entreprise; Dialogue social; Régulation; Syndicat; Types de RSE; regulation; social dialogue; union; works council

Le modèle cybernétique du contrôle de gestion : vers une anthropologie du contrôle de gestion - Bourdages-Sylvain, Marie-Pierre (Relations industrielles / Industrial Relations, 2021)
The article reviews the book, "Le modèle cybernétique du contrôle de gestion : vers une anthropologie du contrôle de gestion," by Benoit Pigé.

The Global Politics of Poverty in Canada: Development Programs and Democracy, 1964-1979 - Bower, Shannon Stunden (Labour / Le Travail, 2021)
The article reviews the book, "The Global Politics of Poverty in Canada: Development Programs and Democracy, 1964-1979," by Will Langford.

Les identités professionnelles des mineurs d’uranium au prisme des transitions industrielles : du régime d’exception au repli identitaire - Breteshé, Sophie; Le Berre, Sylvain (Relations industrielles / Industrial Relations, 2021)
Du point de vue théorique, l’article examine le rapport à l’identité professionnelle dans des contextes de mutations de la filière nucléaire, ce qui requiert un regard rétrospectif sur ces transformations. Par ailleurs, il contribue à la connaissance empirique de la filière uranifère qui est restée pendant de longues années un secteur marqué du sceau du secret militaire. Cet article, qui s’appuie sur une enquête auprès de deux générations de mineurs de l’uranium de l’ouest de la France et l’étude d’archives, analyse l’évolution des identités professionnelles des mineurs d’uranium depuis l’après-guerre jusqu’à la fermeture des mines dans les années 1990. En effet, l’histoire des mines d’uranium n’est pas linéaire et la « mise en intrigue » (Ricoeur, 1983) du passé s’est faite tardivement autour des déchets laissés par l’exploitation, mais en omettant le travail à proprement parler de la mine. Depuis les témoignages d’époque qui présentent l’exploration puis l’exploitation sur le mode du développement économique, en passant par la fermeture puis l’oubli des mines, jusqu’à la prise en compte récente des risques inhérents, l’histoire se révèle plurielle et fragmentée (Brunet, 2004). Ce problème de linéarité repose en partie sur les discontinuités induites à la fois par l’oubli et le travail de mémoire partiel, fait très récemment. À partir de la question de la genèse des identités des mineurs, cet article montre, depuis l’exploration en 1945 jusqu’à la fermeture des mines en 1990, l’évolution de trois éléments structurants de l’identité professionnelle : le contexte institutionnel, le rapport au travail et la nature des relations professionnelles. Si le cas de mineurs d’uranium pose avec force la question du maintien d’une identité dans des contextes de transformation de la filière nucléaire, il met en perspective le rôle des contextes institutionnels sur la nature des relations professionnelles.
Keywords: Identités; Mineurs; Nucléaire; Trajectoire; Uranium

Let Us Rise: Dialectical Thinking, the Commodification of Labour Power, and the Legacy of the Socialist Party of Canada - Campbell, J. Peter (Labour / Le Travail, 2021)
Members of the Socialist Party of Canada (SPC) played a prominent role in the labour revolt of 1919, the One Big Union, and the Winnipeg General Strike. The “failure” of all three has led labour historians to focus on the inability of the party to connect with Canadian workers, an inability fuelled by dogmatism, “impossibilism,” and the exclusion of women and workers of colour. This article turns this approach on its head, pointing out that these events have been unequalled in Canadian history, and seeks to explain why this should be so. It challenges the perception of the party as being wed to evolutionary thinking that caused its members to wait around for the revolution to happen. Instead, it reveals the powerful influence of the dialectical method developed by G. W. F. Hegel; its focus on human action was the philosophical underpinning of the spc’s relentless attack on the wage system and the capitalist system’s commodification of labour power. Far from being “metaphysical” or “otherworldly,” the SPC’s insistence that workers must gain control of the product of their own labour spoke directly to them, including women and workers of colour. In the creation of the One Big Union, in the solidarity of the Winnipeg General Strike, and in the promise of the labour revolt of 1919, we find the legacy of a party committed to workers rising up.
Keywords: Marxism; class; commodification; dialectic; evolution; impossibilism; labour; race; revolution; women

Disrupting Deportability: Transnational Workers Organize - Cardona, Manuel Salamanca (Labour / Le Travail, 2021)
The article reviews the book, "Disrupting Deportability: Transnational Workers Organize," by Leah Vosko.

America’s Other Automakers: A History of the Foreign-Owned Automotive Sector in the United States - Clark, Daniel (Labour / Le Travail, 2021)
The article reviews the book, "America’s Other Automakers: A History of the Foreign-Owned Automotive Sector in the United States," by Timothy Minchin.

The Class Politics of Law: Essays Inspired by Harry Glasbeek - Coulter, Graham (Labour / Le Travail, 2021)
The article reviews the book, "The Class Politics of Law: Essays Inspired by Harry Glasbeek," edited by Eric Tucker and Judy Fudge.

Conférence H.D. Woods : un éclairage par les marges / Conference H.D. Woods: Shedding Light from the Margins - D’Amours, Martine (Relations industrielles / Industrial Relations, 2021)

The Two-Hundred-Million Pound Strike : The 2003 British Airways Walkout - Dabscheck, Braham (Relations industrielles / Industrial Relations, 2021)
The article reviews the book, "The Two-Hundred-Million Pound Strike : The 2003 British Airways Walkout," by Ed Blissett.

La résilience du personnel soignant à l’épreuve de la pandémie de COVID-19 : une étude dans un hôpital public en Tunisie - Dahmani, Amira (Relations industrielles / Industrial Relations, 2021)
Ce travail cherche à appréhender les déterminants de la résilience du personnel soignant dans le contexte de la crise sanitaire Covid-19. Son but est d’accéder à une compréhension profonde des motifs, des forces et des processus à l’oeuvre dans la dynamique complexe de la résilience.
Keywords: COVID-19 health crisis; Résilience; crise sanitaire Covid-19; healthcare staff; hôpital public; personnel soignant; public hospital; qualitative study; resilience; étude qualitative

Les pathologies au travail - Dompierre, Johanne (Relations industrielles / Industrial Relations, 2021)
The article reviews the book, "Les pathologies au travail," by Élisabeth Grebot.

Can Older Workers Be Retrained? Canadian Evidence from Worker-Firm Linked Data - Fang, Tony; Gunderson, Morley; Lee, Byron (Relations industrielles / Industrial Relations, 2021)
Our empirical analysis is based on Statistics Canada’s worker-firm matched data set, the 2003 Workplace and Employee Survey (WES). The sample size is substantial: about 4,000 workers over the age of 50 and 12,000 between the ages of 25 and 49. Training was a focus of the survey, which offers a wealth of worker-related and firm-related training variables. We found that the mean probability of receiving training was 9.3 percentage points higher for younger workers than for older ones. Almost half of the gap is explained by older workers having fewer training-associated characteristics (personal, employment, workplace, human resource practices and occupation/industry/region), and slightly more than half by them having a lower propensity to receive training, this being the gap that remained after we controlled for differences in training-associated characteristics. Their lower propensity to receive training likely reflects the higher opportunity cost of lost wages during the time spent in training, possible higher psychological costs and lower expected benefits due to their shorter remaining work-life and lower productivity gains from training, as discussed in the literature. The lower propensity of older workers to receive training tended to prevail across 54 different training measures, with notable exceptions discussed in detail. We found that older workers can be trained, but their training should be redesigned in several ways: by making instruction slower and self-paced; by assigning hands-on practical exercises; by providing modular training components to be taken in stages; by familiarizing the trainees with new equipment; and by minimizing required reading and amount of material covered. The concept of “one-size-fits- all” does not apply to the design and implementation of training programs for older workers.
Keywords: Canada; older workers; training; worker-firm matched data

Profit Sharing and Workplace Productivity Growth in Canada: Does Teamwork Play a Role? - Fang, Tony; Gunderson, Morley; Long†, Richard (Relations industrielles / Industrial Relations, 2021)
The purpose of this study is to contribute to knowledge of profit-sharing by utilizing a before-and-after analysis of panel data to assess whether the effects of profit-sharing adoption on productivity growth vary, depending on whether a profit-sharing adopter utilizes work teams or not, while controlling for numerous variables that may affect these results within a carefully constructed sample of Canadian establishments. To our knowledge, this is the first study to examine the moderating role of teamwork in the relationship between profit-sharing and productivity growth. Besides the implications for profit-sharing, ascertaining whether profit-sharing and work teams are complementary practices would have important implications for understanding how to develop more effective work teams, a topic of ongoing interest. We utilized a longitudinal research design to compare within-firm productivity growth during the three-year and five-year periods subsequent to profit-sharing adoption and within-firm productivity growth during the same periods in firms that had not adopted profit-sharing. Overall, our results suggest that use of team-based production plays an important moderating role in the success of employee profit-sharing—at least in terms of workplace productivity growth. Establishments that had adopted profit-sharing showed a substantial and highly significant increase in workplace productivity over both the three-year and five-year periods subsequent to adoption, but only if they had work teams. These findings are in line with the notion that work teams help to mitigate potential shirking behaviour in profit-sharing firms (Freeman, Kruse and Blasi, 2010) and are also in line with the argument that work teams serve as an effective mechanism to help translate the purported motivational and other benefits of profit-sharing into tangible productivity gains (Heywood and Jirjahn, 2009).
Keywords: Canada; croissance de la productivité; partage des bénéfices; productivity growth; profit-sharing; work teams; équipes de travail

The Socialist Challenge Today - Fast, Travis (Relations industrielles / Industrial Relations, 2021)
The article reviews the book, "The Socialist Challenge Today," by Leo Panitch and Sam Gindin.

Grève et paix. Une histoire des lois spéciales au Québec - Finkel, Alvin (Labour / Le Travail, 2021)
The article reviews the book, "Grève et paix. Une histoire des lois spéciales au Québec," by Martin Petitclerc and Martin Robert.

The Enchantments of Mammon: How Capitalism Became the Religion of Modernity - Finkel, Alvin (Labour / Le Travail, 2021)
The article reviews the book, "The Enchantments of Mammon: How Capitalism Became the Religion of Modernity," by Eugene McCarraher.

In the Red Corner: The Marxism of José Carlos Mariátegui - Fontes, Yuri Martins (Labour / Le Travail, 2021)
The article reviews the book, "In the Red Corner: The Marxism of José Carlos Mariátegui," by Mike Gonzalez.

Tracking Precarity: Employment Pathways of Precarious Status Migrant Workers in Canada - Foster, Jason (Canadian Journal of Sociology, 2021)
In recent years the issue of migrant workers with precarious status has increased in importance in Canada, in large part due to economic and policy changes that have led to greater numbers of migrant workers remaining in the country post permit expiry. This study tracks the employment experiences of low-skilled migrant workers who arrived through the Temporary Foreign Worker Program and who remained following their permit expiry. Using a temporal analysis, the study identifies four timepoints that shape the workers’ employment outcomes both pre- and post-expiry. Events at these timepoints create differing employment pathways that, in turn, reveal different aspects of the workers’ precarity.  In addition to pathways, workers’ ability to access informal support networks shape their employment outcomes as workers with precarious status.
Keywords: Canada; informal networks; informal workers; irregular migrant workers; precarious employment

J. B. McLachlan Fills Out a Questionnaire, 1931 - Frank, David (Labour / Le Travail, 2021)
Discusses a biographical questionnaire that J.B. McLachlan completed for the Communist International during a visit to the Soviet Union in 1931. In it, the Nova Scotia labour leader briefly responded on his background, education, work and labour activism, political status (including his recruitment to the "Canadian section" of the Communist Party in 1922), and imprisonment in 1923-24. The questionnaire and other related materials came to light as a result of a request made by the author to the Russian State Archives in October 2020.
Keywords: Communist International; Communist Party of Canada; J. B. McLachlan; Nova Scotia coal miners; Trevor Maguire; workers’ autobiographies

Excavating Organizational Assumptions about Cultural Change: The Unintended Consequences of Safety Committee Initiatives - Gosen, Dora; Mielly, Michelle (Relations industrielles / Industrial Relations, 2021)
This study contributes to the emerging literature on the interplay between safety committees and employee perceptions of organizational safety culture. Creating, managing and maintaining a safety culture in organizations involves significant investment in the establishment of safety committees. The role of such committees in improving safety culture perceptions has remained underexplored in the safety management and organizational literature. This study addresses that gap and focuses on a safety committee within the facilities management operations of a large American academic institution. The objective is to generate understandings of how a committee can influence organizational cultural change and impact employee perceptions of safety. Using Schein’s organizational culture model as a prism, we unpack the employees’ implicit cultural beliefs. Data from over sixty employee interviews revealed that formation of the Safety Committee resulted in unintended consequences in terms of employee perceptions. Employees attributed most safety-related actions to the committee when, in fact, the managers and supervisors had actually carried them out. This overestimation of committee activities and concomitant underestimation of managerial actions by employees was an unintended consequence of establishing a committee. Employees, in fact, collectively attributed all positive changes in the organizational culture to the committee. The committee ultimately influenced the employees’ basic assumptions, such change being, according to Schein, a prerequisite for organizational cultural change. This study, therefore, contributes to the literature by proposing that unintended consequences can operate in three different ways to support organizational change. First, unintended consequences can promote positive outcomes; second, they can reveal a new understanding of committees, which under certain circumstances can act as a proxy for management and encourage positive perceptions of managerial commitment. Lastly, unintended consequences can provide a means to detect and ‘excavate’ hidden, implicit assumptions that drive organizational culture’s deepest layers.
Keywords: Schein’s model; comités; committees; conséquences inattendues; culture de sécurité; culture organisationnelle; facilities management; gestion des installations; modèle de Schein; organizational culture; safety culture; unintended consequences

Mot de l’éditeur : Covid 19 : plus qu’une pandémie, une nouvelle ère = Editor foreword: Covid 19 : not a pandemic but a new era - Gould, Anthony Morven (Relations industrielles / Industrial Relations, 2021)
...Ces changements récents entrainent des conséquences assez génériques pour ceux qui pensent et écrivent sur le travail et l’emploi. À travers le monde, les questions urgentes ont toutes une certaine homogénéité. Comment travailler en pratiquant la distanciation sociale ? Comment gérer à distance la main-d’oeuvre ? Qu’advient-il de la productivité si les travailleurs sont dispersés sur des lieux et des horaires différents ? Enfin, dans cette nouvelle réalité, que deviendront la négociation collective et l’asymétrie actuelle entre le capital et le travail ? Voilà autant de questions que nous devons poser et en trouver la réponse. Puis nous devons le faire ensemble, vraiment ensemble, à travers un effort collaboratif mondial. C’est ainsi, je crois, que changera le programme de recherche orthodoxe sur les relations de travail. En tant qu’individus, le défi est d’être en avant de ce qui se passe actuellement et de ne pas s’interroger sur ce qui s’est déjà passé. Voici, donc, ce que la revue entend privilégier : une variété de perspectives sur le plan géographique, une analyse critique, une volonté de tirer des leçons de l’histoire, ainsi qu’une préoccupation constante pour les oubliés et les défavorisés de la nouvelle normalité. Enfin, mon équipe et moi demeureront attachés à une politique de gestion beaucoup plus élargie qui visera l’inclusion et l’adaptation. En gardant ces priorités à l’esprit, je suis fier de présenter les contenus de l’édition 76(3). // These recent lifestyle changes are having somewhat generic consequences for those who think and write about work and employment. The pressing issues throughout the world have a sameness about them. How do jobs get done with social distancing? How are workforces remotely managed? What happens to productivity when workers are geographically dispersed and running on different schedules? Finally, in this new reality, what happens to collective bargaining and the existing capital/labour power asymmetry? We need to ask and answer these questions together—really together—through a collaborative global effort. In this way, I believe, change will come to the orthodox agenda of research on employment relations. As individuals, the challenge is to be ahead of what is happening and not wonder what has happened. Here is what we at the journal are currently emphasizing: geographically diverse perspectives, critical analysis, an emphasis on what history has to teach and an ongoing preoccupation with those who might be left behind and/or disadvantaged by the new normal. Meanwhile, my team and I will continue to be committed to a much broader policy of inclusion and accommodation when it comes to how we manage. It is with these priorities in mind that I am proud to present the content of edition 76(3).

Do Unions Still Matter for Redistribution? Evidence from Canada’s Provinces - Haddow, Rodney (Relations industrielles / Industrial Relations, 2021)
We examine the relationship between union power and redistribution in Canada’s ten provinces between 1986 and 2014. Subnational jurisdictions are thus the focus of research questions that have previously been addressed at the international level. Multilevel models with time-series cross-sectional data are used to estimate the long-term association between union density and redistribution through provincial transfer payments and income taxes. We found that higher union density correlates with considerably more redistribution over the long term but not over the short term. This finding is confirmed by three distinct measures of inequality and poverty reduction, an indication that it is quite robust. The association is significant for the entire study period and for its second half. This finding is consistent with power resource theory in its original form, but not with more recent work in that area or with comparative political economy scholarship, which generally now neglects or downplays the impact of organized labour on social and economic policy outcomes. Our findings suggest a need to re-assess the diminished interest of recent researchers in the political influence of organized labour. It will also interest scholars in other countries where tax and transfer systems are decentralized, and where the impact of organized labour on such measures has been understudied at the subnational level. Additionally, we show that unionized voters in Canada are more favourably disposed than their non-unionized counterparts toward redistribution and toward pro-redistribution political parties. Unions may consequently affect redistribution in part by socializing their members to favour it. This possibility is advanced with preliminary data in this paper. We argue that further scholarly attention is both required and deserved on this subject in Canada and elsewhere.
Keywords: Inequality and poverty reduction; Organized labour and social equity; Power resource theory; Subnational jurisdictions; Time-series cross-sectional analysis; analyse transversale de séries chronologiques; inégalité et réduction de la pauvreté; juridictions infranationales; syndicalisme et équité sociale; théorie des ressources de pouvoir

Ordinary Saints: Women, Work, and Faith in Newfoundland - Hallett, Vicki S. (Labour / Le Travail, 2021)
The article reviews the book, "Ordinary Saints: Women, Work, and Faith in Newfoundland," by Bonnie Morgan.

Understanding Union Commitment Among Young Workers: A Cross-Theoretical Perspective - Hennebert, Marc-Antonin; Fortin-Bergeron, Chloe; Doucet, Olivier (Relations industrielles / Industrial Relations, 2021)
This study aims to shed light on the main determinants of and barriers to union commitment among young workers and, more generally, the relationship young workers have with union life. So far, the relationship between young workers and unionism has been examined mainly in terms of the challenges of access to unionization that confront young workers, a group generally underrepresented in union membership. The more specific issue of union commitment among young workers, once they become unionized, has remained largely underexplored in the literature. Using quantitative and qualitative data from an empirical survey of young unionized workers in the Quebec public service, our study identifies and compares the main factors that explain union commitment among young unionized workers and the theoretical underpinnings. It also seeks to shed light on the barriers to this commitment and identifies the organizational measures that could facilitate union commitment among young workers, based on the perceptions expressed by young union members. Our findings indicate that unions should adopt multidimensional organizational measures to foster union commitment among young workers, with a first step being to increase personalized contact between local union representatives and young members. Such investments at the local level are critical, as shown by our quantitative and qualitative findings. Thus, any reform or measure aimed at encouraging union involvement of young workers should not be limited merely to structural aspects but should also take into account the attitudinal and relational underpinnings of young workers’ commitment to their union. By shifting the focus from youth unionization to young members’ involvement in union bodies, our study will contribute to debate about union representation and the generational renewal of the labour movement’s activist base.
Keywords: Young workers; cross-theoretical perspective; generational renewal; mixed methods; union commitment

Canada’s Other Red Scare: Indigenous Protest and Colonial Encounters During the Global Sixties - Hewitt, Steve (Labour / Le Travail, 2021)
The article reviews the book, "Canada’s Other Red Scare: Indigenous Protest and Colonial Encounters During the Global Sixties," by Scott Rutherford.

The Violence of Work: New Essays in Canadian and US Labour History - High, Steven C. (Labour / Le Travail, 2021)
The article reviews the book, "The Violence of Work: New Essays in Canadian and US Labour History," edited by Jeremy Milloy and Joan Sangster.

Nothing Succeeds Like Failure: The Sad History of American Business Schools - Jeffrey, Muldoon (Relations industrielles / Industrial Relations, 2021)
The article reviews the book, "Nothing Succeeds Like Failure: The Sad History of American Business Schools," by Steven Conn.

Dust versus Dust: Aluminum Therapy and Silicosis in the Canadian and Global Mining Industries - Jorgenson, Mica; Sandlos, John (Canadian Historical Review, 2021)
By the 1930s, silicosis – a debilitating lung disease caused by the inhalation of silica dust – had reached epidemic proportions among miners in the gold-producing Porcupine region of northern Ontario. In response, industrial doctors at the McIntyre Mine began to test aluminum powder as a possible prophylactic against the effects of silica dust. In 1944, the newly created McIntyre Research Foundation began distributing aluminum powder throughout Canada and exported this new therapy to mines across the globe. The practice continued until the 1980s despite a failure to replicate preventative effects of silicosis and emerging evidence of adverse neurological impacts among long-time recipients of aluminum therapy. Situated at the intersection of labour, health, science, and environmental histories, this article argues that aluminum therapy represents an extreme and important example where industry and health researchers collaborated on quick-fix “miracle cures” rather than the systemic (and more expensive) changes to the underground environment necessary to reduce the risk of silicosis.

Do Androids Dream of Electric Cars? Public Transit in the Age of Google, Uber, and Elon Musk - Laforest, Joël (Labour / Le Travail, 2021)
The article reviews the book, "Do Androids Dream of Electric Cars? Public Transit in the Age of Google, Uber, and Elon Musk," by James Wilt.

Formes de solidarité et de mobilisation et modes d’organisation de trois grèves au Québec pour le salaire minimum à 15 $ l’heure - Lafrance, Xavier (Labour / Le Travail, 2021)
Trois grèves qui avaient pour objectif l’obtention du salaire minimum à 15 $ l’heure ont été menées par des syndicats québécois en 2016. Ces grèves se sont inscrites dans des campagnes politiques qui avaient le même objectif. Cet article propose une étude comparée de ces grèves dans le but d’analyser dans quelle mesure les formes de solidarité et les modes d’organisation déployés offrent des pistes de revitalisation qui permettraient au mouvement syndical québécois de relever les défis stratégiques contemporains auxquels fait face le mouvement syndical québécois. L’analyse de ces trois grèves, en s’appuyant sur une typologie des divers syndicalismes et activismes syndicaux, permet d’approfondir les formes de solidarité déployées par les syndicats ainsi que les formes de mobilisation originales qui, toutefois, n’ont pas mené à un progrès substantiel du contrôle démocratique exercé par les membres sur leur mouvement.
Keywords: Alliance de la fonction publique du Canada; Confédération des syndicats nationaux; Fédération des travailleurs et travailleuses du Québec; Modèles de syndicalisme; Service Employees International Union; démocratie syndicale; grève; luttes syndicales; renouveau syndical; salaire minimum

Le régime des décrets de convention collective au Québec. Quel avenir ? - Le Grand Amba Mballa, Albert (Relations industrielles / Industrial Relations, 2021)
The article reviews the book, "Le régime des décrets de convention collective au Québec. Quel avenir ?," by Jean Bernier.

Les intervenants sociaux à l’aune de la nouvelle gestion publique : difficultés émotionnelles, relations professionnelles sous tension et collectifs de travail fragilisés - le Pain, Isabelle; Kirouac, Laurie; Larose-Hébert, Katharine; Namian, Dahlia (Relations industrielles / Industrial Relations, 2021)
L’article présente les résultats d’une étude qualitative menée auprès de 31 intervenants et intervenantes qui travaillent en protection de l’enfance au Québec. Elle porte sur les conséquences des difficultés émotionnelles des intervenants sur leurs relations avec les gestionnaires et les collègues de travail, dans le contexte de la réforme du réseau de la santé et des services sociaux (projet de loi 10). Les résultats montrent qu’une large majorité d’intervenants et intervenantes rapportent une ou plusieurs conséquences délétères dans les relations avec les gestionnaires (colère et frustration, méfiance à l’égard d’une possible instrumentalisation des difficultés émotionnelles, évitement et perte de confiance). Également, une proportion très significative d’entre eux font état de conséquences à l’échelle des relations avec les collègues de travail (isolement et retrait, effet boule de neige sur les collègues et l’équipe de travail et diminution de la collaboration et de l’entraide). L’analyse montre que l’intensification du travail et la dégradation des conditions de pratique des intervenantes et intervenants sociaux, qui ont résulté de la dernière réforme (projet de loi 10) instituée par le ministre Barrette (2013), ont significativement contribué à fragiliser les collectifs de travail. Ce faisant, les possibilités d’entraide et de coopération, pourtant nécessaires à la réalisation de leur mandat professionnel, ont tendance à s’effacer au profit d’une activité professionnelle pratiquée par des travailleuses et travailleurs isolés et en souffrance.
Keywords: Child protection; Collectif de travail; Difficultés émotionnelles; Emotional difficulties; Protection de l’enfance; Reform of healthcare and social services (Bill 10); Relations professionnelles; Réforme de la santé et des services sociaux (projet de loi 10); Work group; Work relationships

The Southern Key: Class, Race and Radicalism in the 1930s and 1940s - Leah, Tony (Labour / Le Travail, 2021)
The article reviews the book, "The Southern Key: Class, Race and Radicalism in the 1930s and 1940s," by Michael Goldfield.

Working-Class Heroes: A History of Struggle in Song - Leier, Mark (James Mark) (Labour / Le Travail, 2021)
The article reviews the book and CD, "Working-Class Heroes: A History of Struggle in Song," edited by Mat Callahan and Yvonne Moore.

Collective Bargaining in Canada in the Age of Precarious Employment - Lewchuk, Wayne (Labour and Industry, 2021)
The decline in the prevalence of the Standard Employment Relationship in Canada has created challenges for Canadian unions. This article reviews the available estimates of the prevalence of precarious employment and gig work in Canada. Using data from the Poverty and Employment Precarity in Southern Ontario (PEPSO) research group it evaluates both the success of unions in organising workers in precarious employment and bargaining for them. The last section reviews recent union strategies to organise workers in precarious employment with a focus on the subset of precarious employment referred to as gig work. Organising gig workers presents unique challenges for unions as many are deemed by their employers as independent contractors and as a result not covered by existing Canadian labour legislation and hence not eligible for union membership. The paper concludes by arguing that organising precarious workers is a work in progress, whose ultimate outcome remains uncertain.
Keywords: Canada; Precarious employment; gig work; unions

Fellow Travellers: Communist Trade Unionism and Industrial Relations on the French Railways, 1914-1939 - Lewis, Robert W. (Labour / Le Travail, 2021)
The article reviews the book, "Fellow Travellers: Communist Trade Unionism and Industrial Relations on the French Railways, 1914-1939," by Thomas Beaumont.

An Experimental Organization of Precarious Professionals: - MacDonald, Ian; Kolhatkar, Manek (Labour / Le Travail, 2021)
This article discusses the sector-wide organization of contractual archaeologists in Québec, beginning with the formation of a workers’ committee and leading subsequently to union accreditation. We theorize the difficulty of organizing these “precarious professionals” and suggest that self-organization outside of an industrial relations framework may be required to overcome barriers to their unionization. Deliberation, norm setting, and informal parlays with employers lead to clarifying class distinctions that professional identification often occludes, while self-organization increases worker confidence in collective action.
Keywords: contractual archaeology; mobilization theory; precarious employment; professional workers; union organizing

Teachers’ Organizations and Educational Reform: Resistance and Beyond - Maharaj, Sachin; Bascia, Nina (Canadian Journal of Educational Administration and Policy / Revue canadienne en administration et politique de l’éducation, 2021)
This paper presents case studies of teacher union-government relationships in three Canadian provinces – British Columbia, Ontario, and Alberta – where teacher organizations have undertaken divergent strategic positions relative to educational reform. It identifies critical factors that may lead teacher unions to challenge government reforms, how and when a teacher organization might instead accommodate governmental reform, and under what circumstances union renewal drives an organization to establish reform strategies of its own. The paper demonstrates the results of these varied strategies and suggests that teacher unions’ stances, including when they are resistant, are rational and, arguably, necessary.
Keywords: educational change; educational reform; politics of education; teacher unions

The University and Social Justice: Struggles Across the Globe - McCartney, Dale M. (Labour / Le Travail, 2021)
The article reviews the book, "The University and Social Justice: Struggles Across the Globe," edited by Aziz Choudry and Salim Vally.

Les relations industrielles en questions - Mohamed, Yasmine (Relations industrielles / Industrial Relations, 2021)
The article reviews the book, "Les relations industrielles en questions," edited by Patrice Jalette.

Mot de l’éditeur : le travail et l’emploi à l’ère de la Covid-19 = Work and Employment in the Era of COVID - Morven Gould, Anthony (Relations industrielles / Industrial Relations, 2021)
/Toute personne qui observe le monde du travail et de l’emploi comprendra que ce volume est mis sous presse à un moment d’incertitude et d’anxiété. En 2020, nous sommes entrés dans une longue période de confinement et d’isolement, la COVID-19 ayant généré plusieurs crises. Comme c’est le cas pour les véritables catastrophes, cette ère de malaise a eu un point de départ bien défini (début de mars 2020), mais elle est maintenant entrée dans une phase qui, malgré le déploiement actuel des vaccins, semble être présente pour une durée indéterminée....//This edition goes to press at a time of uncertainty and anxiety for the majority of those who have a stake in the world of work and employment. In 2020, people on all populated continents entered a protracted period of lockdown and isolation in the wake of the COVID-19 pandemic crisis. As is characteristic of genuine catastrophes, this era of malaise had a defined commencement point (early March 2020) but has now entered a phase where, despite the current roll-out of vaccines, looks like being present for an indeterminate long-haul....

Evil Geniuses: The Unmaking of America: A Recent History - Muldoon, Jeffrey (Relations industrielles / Industrial Relations, 2021)
The article reviews the book, "Evil Geniuses: The Unmaking of America: A Recent History," by Kurt Andersen.

How Innovation Works: And Why It Flourishes in Freedom - Muldoon, Jeffrey (Relations industrielles / Industrial Relations, 2021)
The article reviews the book, "How Innovation Works: And Why It Flourishes in Freedom," by Matt Ridley.

Management Studies in Crisis: Fraud, Deception and Meaningless Research - Muldoon, Jeffrey (Relations industrielles / Industrial Relations, 2021)
The article reviews the book, "Management Studies in Crisis: Fraud, Deception and Meaningless Research," by Dennis Tourish.

Discrimination in the Workplace in Canada: An Intersectional Approach - Nangia, Parveen; Arora, Twinkle (Canadian Journal of Sociology, 2021)
This study examines discrimination in the workplace in Canada and explores the intersection of marginalized groups. It uses data from the General Social Survey 2016, which collected information from 19,609 non-institutionalized individuals. Results show that 17 percent of the job applicants and 9 percent of the workers felt discriminated against in the workplace during the 12 months before the survey. Data analysis indicates that a person’s identification with two marginalized groups increases the chances of discrimination and augments it further with three marginalized identities. However, the incremental effect of four or more marginalized groups is difficult to examine with this dataset due to the depleting sample size with the inclusion of every new group. Results from the logistic regression illustrate that the intersection of two, three, or four selected disadvantaged groups increases workplace discrimination significantly, thus supporting the theory of intersectionality. However, this perspective does not work for some combinations of marginalized groups.
Keywords: Canada; Designated groups; Discrimination; Intersectional discrimination; Job application; Marginal groups; Workplace

Punishing Poverty: How Bail and Pretrial Detention Fuel Inequalities in the Criminal Justice System - Newport, Melanie D. (Labour / Le Travail, 2021)
The article reviews the book, "Punishing Poverty: How Bail and Pretrial Detention Fuel Inequalities in the Criminal Justice System," by Christine Scott-Hayward and Henry F. Fradella.

Personnels navigants : un collectif de travail à l’épreuve du changement - Nogues, Sarah; Tremblay, Diane-Gabrielle; Mansour, Sari (Relations industrielles / Industrial Relations, 2021)
Notre article porte sur les intensités et la fragilisation des collectifs de travail et offre une synthèse de la littérature concernant le travail et ses intensités, en particulier dans le milieu aérien. Prenant le cas du personnel navigant commercial (PNC) dans le milieu aérien, nous nous appuyons sur la théorie des demandes-ressources du travail et de l’organisation capacitante pour analyser les perceptions de ces travailleurs concernant les demandes physiques, psychosociales et organisationnelles du travail, ainsi que les ressources de même type, notamment à la suite de l’autorisation d’une réduction d’effectif par le ministère des Transports sur bon nombre de porteurs canadiens en juillet 2015. Nous portons une attention particulière aux demandes du travail constituant une contrainte, ce qui est rarement pris en compte dans les études sur l’intensification du travail. À l’aide du construit de caravanes de ressources et d’organisation capacitante, nous nous demandons si les collectifs de travail PNC sont en mesure d’accomplir leur mission collective de maintien de la sécurité et de service auprès du public. Nous avons pour cela mené 41 entrevues semi-dirigées auprès d’agents de bord et de directeurs de vol volontaires provenant de deux compagnies aériennes canadiennes. Nous avons procédé à une analyse de contenu qualitative faisant émerger les thèmes principaux de manière inductive et analysant les demandes et les ressources physiques, psychosociales et organisationnelles du travail. Nos résultats documentent de façon originale comment une augmentation notable des intensités contraignantes du travail perturbe les collectifs de travail, en particulier le rôle pivot du directeur de vol, contribuant à la recherche émergente au sujet de la fragilisation des processus de travail. De nombreux aspects demeurent à améliorer pour qualifier les compagnies aériennes étudiées d’organisations capacitantes.
Keywords: airline safety; cabin crew; capacitating organization; demandes-ressources du travail; demands-resources; fragilisation; fragilization; gestion des ressources humaines; human resource management; intensification du travail; intensification of work; organisation capacitante; personnel navigant; sécurité aérienne; work

Precarious Employment in Canada - Ornstein, Michael (Canadian Journal of Sociology, 2021)
Detailed analysis of Statistics Canada Labour Force Survey shows the complex relationship between the different types of non-standard employment, including non-permanent jobs, self-employment, part-time work and low pay. Term and contract work has increased substantially since 1997, but there is no corresponding decrease in permanent jobs or increase in part-time or low wage jobs. The different forms of non-standard employment are concentrated in specific population groups, including women in part-time and low wage jobs, university graduates and younger workers in term and contract jobs, and older workers in self-employment. But precarious employment is much more strongly related to occupation and industry than to workers’ characteristics. There are some provincial differences, while firm and establishment size and unionization have small effects on non-standard employment. These findings cast doubt on the dominant narrative of precarious employment.
Keywords: Canada; industry; occupation; part-time work; precarious employment

Canadian Communism at the Crossroads, 1956–1957: An Introduction - Palmer, Bryan D. (Labour / Le Travail, 2021)
Analyzes the crisis in Canadian Communism triggered by international developments including Soviet leader Nikita Khrushchev's denunciation of the crimes of the Stalin era made in a "secret speech" in February 1956, and the Soviet Union's intervention later in the year to crush the revolt in Hungary. Calls attention to Karen Levine's article, "The Labor-Progressive Party in Crisis, 1956-1957, " published in the same issue, that was originally written as an undergraduate essay at the University of Toronto in the late 1970s.
Keywords: 1956; 20th Congress of the Communist Party of the Soviet Union; Anti-Semitism; Canadian Communism; Gui Caron; J.B. Salsberg; Joseph Stalin; Labor-Progressive Party; Nikita Khrushchev; Norman Penner; Stanley B. Ryerson; Tim Buck

Institutional Experimentation, Directed Devolution and the Search for Policy Innovation - Peetz, David (Relations industrielles / Industrial Relations, 2021)
One response to the employer’s search for “flexibility” (most evident in the “platform economy”) may be “institutional experimentation,” i.e., changes to institutions and how they relate to organizations and labour standards. Our question: “What form of institutional arrangement can best enable the lessons of policy experimentation to be learned and disseminated?” Under directed devolution, as proposed here, legal entitlements or obligations would be set at a higher level (say, a national jurisdiction). A lower level (“subsidiary bodies”) would be required to work out detailed implementation of those standards, with a view to protecting the affected workers’ interests. The subsidiary bodies might cover specific industries or groups of industries. They may need to be quite innovative. Results would be evaluated and ideas generated. By emphasizing flexibility and learning, directed devolution enables actors to learn from the experiments of other actors. One such example is the regulation of New York’s road passenger transport industry in 2019, a highly innovative attempt to convert a high-level time-based minimum standard into a practical, local solution. Directed devolution is a form of multi-level policy-making, with some similarities to the concept of subsidiarity, but more tightly integrated. Other relevant but distinct forms of multi-level bargaining include the ILO Conventions, the Bangladesh Accord and several forms of regulation adopted in Australia. Actors and policy-makers should have long-term strategies, be careful in their processes of selecting institutional members, and be prepared to deal with powerful opposition. Directed devolution can be useful wherever establishing enforceable general principles is important and can make a real difference, but there are complications with implementation if circumstances vary considerably among organizations or industries. Devolution can be achieved without losing enforceability, and this can be done without shifting power away from those with less power. Directed devolution is a complement to, not a substitute for, specific regulatory interventions.
Keywords: directed devolution; disruption; décentralisation dirigée; expérimentation institutionnelle; flexibility; flexibilité; institutional experimentation; perturbation; platform economy; regulation; réglementation; économie de plate-forme

Strategies Used by Middle Managers to Support Employees Carrying Out Emotionally Demanding Work: Which Strategies and Why Those Ones? - Pelletier-Bosshard, Emma; Freeman, Andrew; Jauvin, Nathalie; Côté, Nancy (Relations industrielles / Industrial Relations, 2021)
Many areas of practice in health and social services are emotionally demanding. This type of work can be associated with psychological health problems and middle managers play a key role in reducing such risks for their staff. Although the importance of providing this support is recognized, attaining such an objective is not necessarily straightforward because of the multiple demands that managers must juggle. Using an ergonomic perspective, this qualitative research study, which was conducted in a regional child protection service in Quebec (Canada), aimed to identify the strategies used by middle managers to support staff whose work is considered emotionally demanding. The results reveal that managers use a range of support strategies, which fall into seven categories. Although the strategies are distributed along two axes, proximity (direct, indirect) and time (short-term, long-term), they tend to be more direct and short-term (e.g., provide emotional support). The choice of strategies is influenced by various facilitating or constraining organizational, interpersonal and individual factors. A strong influence appears to be time availability. This study provides a detailed picture of the strategies used by middle man-agers and the complexity with which these individuals are confronted in providing their staff with support. Further research is required, for example, to better understand the impact of certain factors on the choice of support strategies and to evaluate the impact of support strategies from a staff perspective.
Keywords: contexte de pratique des services sociaux et de santé; health and social service practice context; organizational strategies; stratégies de soutien; stratégies organisationnelles; support strategies

Automation and the Future of Work - Penner, Mack (Labour / Le Travail, 2021)
The article reviews the book, "Automation and the Future of Work," by Aaron Benanav.

Les conditions de performativité du discours autour de la création de valeur partagée - Persais, Eric (Relations industrielles / Industrial Relations, 2021)
Le concept de création de valeur partagée (Creating Shared Value, CSV) proposé par Porter et Kramer ne fait pas l’unanimité au sein de la communauté scientifique. Pourtant, il bénéficie d’une certaine popularité chez les chefs d’entreprises qui voient dans ce concept le moyen de répondre efficacement aux enjeux du développement durable et indirectement de réconcilier économie, social et écologie. Si l’utilisation de la CSV dans les déclarations du dirigeant permet de rassurer l’ensemble des parties prenantes sur l’objectif poursuivi par l’entreprise, celle-ci ne trouve pas obligatoirement des effets dans les pratiques organisationnelles. Basant sa recherche sur une étude de cas unique inscrite dans une perspective longitudinale, l’auteur s’intéresse ici au passage du discours aux actes. Il s’interroge sur le caractère performatif de la CSV et met en évidence des conditions de performativité spécifiques au discours sur la création de valeur partagée. Au terme de cette recherche, trois facteurs ont pu être mis en évidence comme des éléments facilitateurs : l’absence de théorie concurrente, la mise en oeuvre d’un processus d’acceptation sociale, l’inscription de la CSV dans une perspective plus globale touchant à la raison d’être de l’entreprise. Les résultats ainsi obtenus, qui devront cependant être confirmés par une étude à plus grande échelle, complètent les travaux précédents sur les conditions de performativité du discours stratégique en l’adaptant au concept de CSV aujourd’hui largement utilisé dans les milieux d’affaires.
Keywords: Corporate Social Responsibility (CSR); Creating Shared Value (CSV); création de valeur partagée; performativity; performativité; responsabilité sociétale de l’entreprise (RSE); sustainable development

Un encadrement de proximité en recomposition : Les « managers de rayon » dans la grande distribution - Racine, Florent (Relations industrielles / Industrial Relations, 2021)
Cet article porte sur les salariés des grandes surfaces alimentaires en France. Si la littérature existante sur le secteur porte essentiellement sur les caissières et utilise la monographie, notre approche s’intéresse aux managers de rayon. Porter le regard sur les managers de rayon, premier niveau d’encadrement en magasin, permet de mieux comprendre les logiques qui traversent le secteur. Mais contrairement à l’approche habituelle qui utilise la monographie, notre approche combine les échelles d’analyse (micro, méso et macro) afin d’ancrer les observations du terrain au sein de l’histoire sectorielle et de la conjoncture. Cela nous conduits à associer la sociologie du travail et de l’emploi avec la sociologie des groupes professionnels pour montrer que les managers travaillent au sein de deux principaux segments professionnels : les rayons alimentaires, d’une part, et les rayons non alimentaires, d’autre part. Sur chaque segment, les conditions de travail ne sont pas tout à fait les mêmes : la situation économique des groupes intégrés étant préoccupante, ces derniers ont procédé à une réorganisation des rayons. Par conséquent, les conditions d’emploi sont également différentes. En effet, si le processus de centralisation-décentralisation des tâches et la sélection d’un nouveau profil de managers sont bien mis en oeuvre de façon homogène dans les rayons alimentaires, deux rayons non alimentaires conservent leur particularité. Au rayon parapharmacie tout d’abord, le titre de docteur constitue une barrière à l’entrée dans ce marché du travail fermé. Parallèlement, les récentes réorganisations permettent à ce dernier de s’emparer des rayons des collègues, faisant de ce manager le grand gagnant des mutations actuelles. Aux rayons brun-blanc-gris ensuite, les managers sont dans une situation plus difficile : plus que partout ailleurs, ces rayons qui perdent de l’argent ont été réorganisés ou supprimés, annonçant la « mort » progressive de ce groupe.
Keywords: department managers; emploi; employment; labour; managers de rayon; organisation du travail; professional segments; segments professionnels; travail; work organization

Pour elles toutes : femmes contre la prison - Rech, Nathalie (Labour / Le Travail, 2021)
The article reviews the book, "Pour elles toutes : femmes contre la prison," by Gwenola Ricordeau.

The Responsible Professor: EAPs and the Neoliberal University - Reuter, Shelley Zipora (Canadian Journal of Sociology, 2021)
Universities commonly engage Employee Assistance Programs to help workers with their problems. In this institutional case study of neoliberalism in action, I analyze the EAP newsletters from one Canadian institution I call “Corporate U” for their impact on full-time tenured and tenure-track faculty. I show how their messaging counterproductively amplifies pressures in today’s university to be resilient and perform and be accountable. I take the EAP to be an agent of the university, and as such, their newsletters demonstrate the rise of neoliberal managerialism in academic life. Of particular concern is their individualising tendency to construct “the responsible professor” as an ideal to which all academic workers must now aspire.
Keywords: performance

Sessional Contract Faculty, Unionization, and Academic Freedom - Ross, Stephanie; Savage, Larry; Watson, James (Canadian Journal of Higher Education / Revue canadienne d'enseignement supérieur, 2021)
This article explores the relationship between unionization and academic freedom protections for sessional faculty in Ontario universities. Specifically, we compare university policies and contract provisions with a view to determining whether unionized sessionals hired on a per-course basis have stronger academic freedom protections than their non-union counterparts. We then explore whether particular kinds of bargaining unit structures are more conducive to achieving stronger academic freedom provisions. Finally, we consider whether academic freedom can be exercised effectively by sessionals, whether unionized or not. We conclude that unionization does help to produce stronger academic freedom protections for sessional faculty and that faculty association bargaining unit structures are most likely to help deliver this outcome. We further conclude that academic freedom is difficult to exercise for sessional faculty, regardless of union status, but that unionization offers greater protections for sessionals facing repercussions as a result of asserting their academic freedom.
Keywords: academic freedom; associations de professeurs d’université; bargaining unit structures; chargés de cours; contract faculty; enseignants contractuels; faculty associations; liberté académique; sessional instructors; structures d’unités de négociation; syndicats; unions

The Shock Doctrine Comes to Canada: Laurentian University’s Insolvency Claim and the Neoliberal Tide - Roth, Reuben (Critical Sociology, 2021)
During the depths of COVID-19, Laurentian University, a small Canadian postsecondary institution located in the mid-sized city of Sudbury Canada, declared that it was insolvent and was legally allowed to terminate one-third of its faculty and cut almost one-half of its academic programmes. This historically unprecedented attack on a Canadian public institution utilized a Federal corporate court process, the Companies’ Creditors Arrangement Act (CCAA), a piece of legislation akin to the US Chapter 11 process. The result of the still-ongoing process saw the university Administration and Board of Governors working against the interests of the community, targeting the arts, Indigenous, Francophone and working-class communities. This article poses the question ‘to whom do universities belong, and at what point does a publicly funded university stop being a collective “social good” – responsible to the society that spawned it – and start being a stand-alone organization that serves private interests?’
https://www.researchgate.net/publication/354900893_The_Shock_Doctrine_Comes_to_Canada_Laurentian_University's_Insolvency_Claim_and_the_Neoliberal_Tide
Keywords: Companies’ Creditors Arrangement Act; academic labour; austerity; neoliberalism; privatization

Upon the Altar of Work: Child Labor and the Rise of a New American Sectionalism - Rouleau, Brian (Labour / Le Travail, 2021)
The article reviews the book, "Upon the Altar of Work: Child Labor and the Rise of a New American Sectionalism," by Betsy Wood.

Editors’ Note / Note de la rédaction - Sangster, Joan; Smith, Charles W. (Labour / Le Travail, 2021)
Considers the human and financial cost of the 1918-19 flu pandemic versus the Covid-19 pandemic. Pays tribute to the late Leo Panitch, to whom the volume is dedicated. Comments on articles in the issue and notes that they emphasize the importance of all forms of work and organization. Deplores the rise of market-driven universities and the cuts at Laurentian University. Welcomes Kirk Niergarth as co-editor, which helps pave the way for Joan Sangster's retirement as co-editor.

The Legacy of Leo Panitch - Sangster, Joan; Smith, Charles W.; Warskett, Rosemary; Blanc, Eric; Konings, Martijn; Maher, Stephen; Ross, Stephanie (Labour / Le Travail, 2021)
Introduced by editors Sangster and Smith, this roundtable offers papers by former students of Panitch on his multifaceted legacy. Themes include Panitch as organic intellectual (Warskett), the fall and future of social democracy (Blanc), money and the critique of capitalism between political sociology and political economy (Konings), Panitch and the practice of socialist mentorship (Maher), and Panitch as a transformative teacher (Ross).
Keywords: Leo Panitch; activist; class struggle; global scholar; labour; legacy; scholar; social democracy; socialism

Organized Labour and the NDP: Looking Back on Sixty Years of Party-Union Relations - Savage, Larry (Labour / Le Travail, 2021)
This article begins with a broad overview of the scholarly literature on labour politics in Canada before focusing more specifically on the relationship between organized labour and the NDP. The article is organized thematically, focusing on three key features of the party-union relationship: (1) institutional ties between labour and the NDP; (2) the ideological impact of labour on the politics of the NDP: and (3) labour's (in)ability to deliver votes to the party. Each dimension of the party-union relationship reveals factors that contributed to a loosening of ties over time and sets the stage for a final concluding section exploring the implications of a weakened NDP-union link for the future of labour and working-class politics in Canada. –From author's introduction
Keywords: New Democratic Party; labour politics; party-union relations; social democracy; unions

Workload, workplace violence and harassment, and well-being of personal support workers in home and community care - Sayin, Firat; Denton, Margaret; Brookman, Catherine; Davies, Sharon; Zeytinoglu, Isik (Relations industrielles / Industrial Relations, 2021)
Demand for home and community care services has continuously increased in Canada and elsewhere in the last few decades due to aging of the population and healthcare policy changes shaped by budgetary limitations. As a result, home and community care organizations are having trouble hiring adequate numbers of healthcare workers to meet the escalating demand, the result being increased workload on these workers. Another stream of literature has shown that care recipients and their family members, frustrated with the limited ability of healthcare workers to provide adequate care because of increased workload, might resort to violence and harassment. Bringing these two streams of literature together, we examined the relationships among three variables : workload ; workplace violence and harassment ; and well-being of personal support workers (PSWs). Using structural equation modeling, we analyzed a 2015 Ontario-wide survey of 1,347 PSWs employed in the home and community care sector. The results indicate that workload is negatively associated with extrinsic and intrinsic job satisfaction, and this relationship is mediated by violence and harassment and by stress. Specifically, workload is positively associated with violence and harassment at work, which in turn is positively associated with stress, which in turn is negatively associated with extrinsic and intrinsic job satisfaction. Our study contributes to the literature by examining the impact of a work environment factor, workload, on the well-being of PSWs. This approach makes it possible to expand the current literature’s focus on psychological processes at the individual level to a more contextual approach. Furthermore, the results have important implications for home and community care organizations as well as for the healthcare sector in general. The well-being of PSWs is critical to retaining them and to ensuring the quality of care they provide their clients. Thus, their workload should be lowered to a more manageable level to help minimize the violence and harassment they experience.
Keywords: Canada; extrinsic job satisfaction; healthcare workers; intrinsic job satisfaction; personnel de santé; satisfaction extrinsèque au travail; satisfaction intrinsèque au travail; stress

Balayons les abus : expérience d’organisation syndicale dans le nettoyage - Simonet, Maud (Labour / Le Travail, 2021)
The article reviews the book, "Balayons les abus : expérience d’organisation syndicale dans le nettoyage," by Marielle Benchehboune.

Change and Continuity: Canadian Political Economy in the New Millennium - Smith, Charles W. (Labour / Le Travail, 2021)
The article reviews the book, "Change and Continuity: Canadian Political Economy in the New Millennium," edited by Mark P. Thomas, Leah F. Vosko, Carlo Fanelli, and Olena Lyubchenko.

Remembering Wayne Roberts, 1944–2021 - Sobel, David (Labour / Le Travail, 2021)
Obituary for Wayne Roberts (1944-2021), a Labour/Le Travail contributor who wrote on labour, food policy, the environment, and urban issues.

Une histoire politique du tiers-monde - Sondarjee, Maïka (Labour / Le Travail, 2021)
The article reviews the book, "Une histoire politique du tiers-monde," by Vijay Prashad.

The Death Penalty and Sex Murder in Canadian History - Swainger, Jonathan (Labour / Le Travail, 2021)
The article reviews the book, "The Death Penalty and Sex Murder in Canadian History," by Carolyn Strange.

Technological Strikebreaking: A Case Study of Quebec’s Anti-Scab Legislation - Talarico, Andrea (Relations industrielles / Industrial Relations, 2021)
The right to strike has been constitutionally protected in Canada since 2015. In other jurisdictions where the right to strike is explicitly recognized in the constitution, protection against strikebreaking is recognized as part of that right. Only two Canadian provinces restrict the use of replacement workers during a strike or a lockout. Quebec’s Labour Code has provisions that prohibit the use of replacement workers at the employer’s establishment. Quebec arbitrators, courts, and boards have interpreted this ill-defined concept as a strictly physical location of production, while ignoring technological advances that make remote work possible. This paper examines how the restrictive interpretation of establishment allows a form of strikebreaking that the Spanish Constitutional Court has described as “technological strikebreaking” (esquirolaje technologico), while also allowing the use of technology already at the employer’s disposal to circumvent restrictions on replacement workers even when such technology is not routinely used. The impact of technology on strikebreaking is examined through two case studies: the successive lockouts at the Journal de Québec and the Journal de Montréal. In both cases, external contributors provided the newspapers with content electronically, thus allowing uninterrupted publication. Using Katz, Kochan and Colvil’s three-tier model of collective bargaining, this paper looks at how technological strikebreaking disrupts not only the balance of bargaining power but also bargaining strategy, and how, in the case of the Journal de Montréal, it led to devastating bargaining outcomes. Though the lockouts led to a call for legislative reform in 2011, legislative change is not necessary to align existing provisions with the goal of shortening labour disputes.
Keywords: lockout; replacement workers; right to strike; technological strikebreaking

Should I Stay or Should I Go Home? Newcomer Employment Experiences in Mid-Sized Canadian Cities - Thomas, Jasmine (Canadian Journal of Sociology, 2021)
Despite changes to Canadian immigration policy to address declining labour market outcomes, many highly educated immigrants still face challenges when searching for career-related employment. Semi-structured interviews with 38 newcomer professionals in Edmonton, Alberta and Winnipeg, Manitoba illustrate significant obstacles including a lack of credential recognition, racial discrimination and a requirement for Canadian experience. Drawing from intersectional feminism and critical race theory, this study assesses the perspectives of newcomers during their employment search and explores the common desire for return-migration. Findings illustrate how the pre-arrival expectations of immigrants are incongruent with the realities of persistent labour market barriers. Newcomers consider if they should stay in Canada due to the lack of meaningful economic opportunities.
Keywords: critical race theory; intersectionality; labour market integration; labour market segmentation; transnational feminism

Cabin Crew Conflict: The British Airways Dispute, 2009–11 - Tiemeyer, Phil (Labour / Le Travail, 2021)
The article reviews the book, "Cabin Crew Conflict: The British Airways Dispute, 2009–11," by Phil Taylor and Sian Moore.

Corvée Labour and the Habitant “Spirit of Mutiny” in New France, 1688–1731 - Tomczak, Richard H. (Labour / Le Travail, 2021)
The article examines the evolution of Canadian corvée labour in the late 17th- and early 18th-century French Empire. In New France, tenants, referred to as habitants, rented land from seigneurs in exchange for several taxes. The labour tax, or corvée, required habitants to work on their seigneur’s estate for one to two days a year. Additionally, habitants were responsible for providing corvée for building any public infrastructure that the community required. From the Nine Years’ War (starting in 1688) to the construction of the Chemin du Roy (1732), colonial officials experimented with mass corvée labour mobilization in Canada. A number of factors allowed habitants to challenge authority when they felt the colonial élite had violated their right to subsistence. When drafted annually into forced labour for the construction of Québec and Montréal’s fortifications, groups of habitants refused to show up for work, called upon their superiors to protect them from service, or collectively discussed mutiny if conditions did not improve. During the first three decades of the 18th century, corvée was a negotiated process, with habitants constantly putting forth their own definitions of acceptable labour mobilization.
Keywords: New France; Québec; corvée; habitants; labour history; mutiny; protest; seigneurial system

Promenade sur Marx. Du côté des héroïnes - Toupin, Louise (Labour / Le Travail, 2021)
The article reviews the book, "Promenade sur Marx. Du côté des héroïnes," by Valérie Lefebvre-Faucher.

New Geographies of Racism: Urbanization, the Biopolitical, and Racial Capitalism - Tretter, Eliot (Labour / Le Travail, 2021)
The article reviews and comments on the books, "Indigenous in the City: Contemporary Identities and Cultural Innovation," edited by Evelyn Peters and Chris Anderson, "Displacing Blackness: Planning, Power, and Race in Twentieth-Century Halifax," by Ted Rutland, "Stolen City: Racial Capitalism and the Making of Winnipeg," by Owen Toews, and "Dead Labor: Toward a Political Economy of Premature Death," by James Tyner.

Farewell, Ed Finn: An Early Labour/Le Travail Board Member Who Used Critical Thought and Journalistic Skill to Expose Wrongdoing - Verzuh, Ron (Labour / Le Travail, 2021)
Obituary for Ed Finn (1926-2000), journalist, editor, trade unionist, and first leader of the Newfoundland and Labrador NDP.

Internet Platform Employment in China: Legal Challenges and Implications for Gig Workers through the Lens of Court Decisions - Wang, Tianyu; Cooke, Fang (Relations industrielles / Industrial Relations, 2021)
Research Objective and Questions: We aimed to examine court rulings on disputes between network platforms and labour providers in order to understand the nature of the employment relations and the broader consequences for society as a whole. We addressed two questions: What is the attitude and role of the courts in resolving disputes between Internet network platforms and labour providers in China within a civil law system? What are the prospects that legal innovations will improve protection for platform labour providers who fall outside the scope of labour law, in order to counter the unregulated expansion of digital capitalism at the expense of the under-/unprotected? Methodology: We primarily used secondary data, namely 102 publicly available Court decisions from 2014 to 2019. The case decision reports were downloaded from the Supreme People’s Court “Network of Court Decision Papers.” Results: Disputes occurred mainly in cities that have the most developed platforms and an independent worker model of employment. They mainly involved network platforms that provide such services as driving, food delivery and courier services. All of the disputes involved road accidents, and over half occurred in Beijing and Shanghai—two leading cities in China that have dense populations. Dispute cases rose sharply, peaked in 2017, started to drop in 2018 and fell even more in 2019. The disputes seem to have educated people on both sides, with the result that more precautions are being taken. Contributions: Our study makes three contributions. First, we identified three types of platform employment in China, the motives of the platforms in their choice of labour utilization and the legal implications in terms of labour and third-party protection. Second, we examined the attitude and role of the courts in judging disputes between network platforms and labour providers within legal constraints. Third, we propose that socialization of contract service should be central to platform employment.
Keywords: China; court decisions; gig economy; legal challenges; platform employment; subordination theory

The Chronology of Revolution: Communism, Culture, and Civil Society in Twentieth-Century Britain - Weesjes, Elke (Labour / Le Travail, 2021)
The article reviews the book, "The Chronology of Revolution: Communism, Culture, and Civil Society in Twentieth-Century Britain," by Ben Harker.

In Memoriam: Leo Panitch, 1945–2020 - Whitaker, Reginald (Labour / Le Travail, 2021)
Pays homage to Panitch's life and work as an activist, academic, and writer. Discusses Panitch's origins in Winnipeg's left-wing Jewish community, his tutelage as a graduate student under Ralph Miliband in England, and his wide-ranging engagement as a Marxist political scientist. The author also reflects on his near half-century friendship with Panitch that began in London, England, in 1972.

The Long Deep Grudge: A Story of Big Capital, Radical Labor, and Class War in the American Heartland - Wood, Gregory (Labour / Le Travail, 2021)
The article reviews the book, "The Long Deep Grudge: A Story of Big Capital, Radical Labor, and Class War in the American Heartland," by Toni Gilpin.

Family Responsibilities and Silence of Rural Migrant Workers in China: The Role of Town-Fellow Organizations - Yuan, Fang; Cooke, Fang Lee; Zhong, Teng; An, Fansuo (Relations industrielles / Industrial Relations, 2021)
Employee voice in China remains an under-researched topic from an industrial relations perspective. We investigated the relationship between family dependents (children and elderly) and migrant worker silence, with town-fellow organizations as a moderator, based on the data of the 2014 Guangdong Migrant Workers Survey. The findings reveal that migrant workers with dependent children are more likely to keep silent when their labour rights and interests are violated at the workplace, while family responsibilities for dependent elderly family members do not have significant impacts on migrant workers’ silence. In addition, town-fellow organizations weaken the association between family responsibilities for elderly dependents and silence. Our study contributes to the existing literature on employee voice and provides evidence on the role of town-fellow organizations in China as an informal, emerging institutional actor that regulates labour relations through their involvement in dispute resolution.
Keywords: acteur institutionnel informel; employee silence; family dependents; informal institutional actor; membres de famille à charge; migrant workers; organisation de migrants venus de la même ville; silence de l’employé; town-fellow organization; travailleurs migrants

A Fistful of Shells: West Africa from the Rise of the Slave Trade to the Age of Revolution - Zachernuk, Philip S. (Labour / Le Travail, 2021)
The article reviews the book, "A Fistful of Shells: West Africa from the Rise of the Slave Trade to the Age of Revolution," by Toby Green.